Performance IEEE 802.14.5 and zigbee protocol on realtime monitoring augmented reality based wireless sensor network system - Arda Surya Editya; Surya Sumpeno; Istas Pratomo (Universitas Ahmad Dahlan, 2017)
The internet of Thing (IoT)technology has much development in this era. It has various wireless media transmission systems such as ESP and XBEE. Some IoT device can monitor website or application. On the other hand, Augmented Reality (AR) is a technology that used more on the entertainment sector. Here, we try to use AR to monitor the xbee based IoT device. As a result, there is the different result between Zigbee Protocol and IEEE 802.14.5 real time monitoring system. The optimum estimation of realtime time tolerance of those monitoring systems is >1500 ms (IEEE 804.14.5) and > 50 ms (Zigbee protocol).